Analysis of the Potential for Implementing an Electronic Road Pricing (ERP) System on National Roads in Bandung City - Arrahman, Wildan; Nizami, Mochamad Rifky; Anggara, Dendy; Novriani, Shinta (Indonesian Journal of Advanced Research, 2025)
Traffic congestion is a common problem in developing countries including Indonesia, especially in dense urban areas such as Bandung City. This study analyzes the potential for the implementation of Electronic Road Pricing (ERP) on Jl. Soekarno Hatta (Gedebage Intersection - Cibiru Roundabout), Bandung City. Traffic characteristics show a Saturation Degree (DJ) value of 0.85 in the morning and afternoon and 0.75 in the afternoon, with Level of Service (LoS) E and D. Congestion costs reach Rp 47,710,714 (morning), Rp 55,759,813 (afternoon), and Rp 75,905,411 (afternoon) per hour. The results show that the implementation of Electronic Road Pricing (ERP) system can reduce the use of private vehicles and increase the efficiency of congestion costs. Thus, the Electronic Road Pricing (ERP) system is a relevant travel demand management strategy in urban areas of Indonesia.